Hubungan Media Pembelajaran dan Minat Siswa pada Mata Pelajaran IPS - Nahdatul Hazmi; Ade Kurnia (Kaganga:Jurnal Pendidikan Sejarah dan Riset Sosial Humaniora, 2022)
The purpose of the study was to determine the relationship between learning media and students' interest in learning in integrated social studies subjects in grade 8 at SMPN 2 Kec. Situjuah Limo Nagari. The research method uses quantitative research with a correlation approach. Data collection techniques used by researchers include observation and questionnaires. The result of the research shows that based on all the items in the question, it can be 3.77. This means that the learning media and students' interest in learning are not running as they should be from what is expected. From the results of hypothesis testing and data processing, there is a relationship between learning media and student interest in learning so that the coefficient price between x and y is 0.77 which means it is in the strong category. The conclusion from the research is that the relationship between learning media and students' interest in learning is good enough to support learning activities in Integrated Social Studies (IPS) subjects. Keywords: Interest in learning, Learning Media